Gross-anatomical and.osteometric investigations on sternum in quails - Ozkan, ZE (Indian Veterinary Journal, 2004)
The osteological structure changes according to the flying, running and swimming abilities in avians. The quails are flying and running birds and belong to the Phasianidae family order Galliformes (Austin et al., 1975; Demirsoy, 1998). There are some anatomical studies on the sternum in wild and domestic avians (Ozkan, 1996; Samejima et al., 1989) but macro-anatomical features on sternum in quails have not been investigated in detail. The aim of this. study is to investigate the gross anatomical features of the sternum in quails and to contribute to the lack of information in this field.